Early detection of problem implants using infrared thermography - Spire, M.F.; Galland, J.C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thermal imaging of feedlot cattle ears is a noninvasive diagnostic tool that aids in identifying properly placed or abscessed growth-promoting implants. Thirty-two calves were used to determine if abscessed and normal, functional implants could be identified and differentiated using infrared thermography. Infrared images were taken at implantation on days 2, 4, 7, 14, and 21 after implantation. Abscessed implants were easily identified. Use of thermal imaging can verify implant administration and, thus, has the potential to immediately impact feedlot quality assurance programs.
Keywords: Beef; Infrared thermography; Feedlot cattle